Related Videos

Expand the expression $\left(x-1\right)^2$

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Pre-Calculus - Condensing a logarithmic expression to one logarithm 2[3lnx - ln(x+1)-ln(x-1)]

https://www.youtube.com/watch?v=HS0--oEAT4I

Tutorial - Evaluate an expression with two variables ex1, (3x - y)^2; x = 4; y = 1

https://www.youtube.com/watch?v=a_CH5WrNBYQ

How to rewrite a logarithmic expression as one single logarithm

https://www.youtube.com/watch?v=JWI06mfSrh0

Special products of the form (x+a)(x-a) | Algebra I | High School Math | Khan Academy

https://www.youtube.com/watch?v=JfuisfEdnjk

Algebra 2 - How to solve rational equations, (1/x) - (2/(x + 3)) = 0

https://www.youtube.com/watch?v=EvdNv1r0r9U

Algebra 1 - Simplify expressions with exponents, (y^2 z)(yz)^2

https://www.youtube.com/watch?v=RUxCZirqYLI
$\left(x-1\right)^2$

Main topic:

Special products

Time to solve it:

~ 0.02 s